Spatial Scientometrics in Measuring the Geography of Knowledge and Innovation: The Case of India - Андрей Сергеевич Михайлов (Экономика региона, 2025)
The global landscape of science, technology, and innovation (STI) is increasingly shifting toward developing countries. China and India—two Asian economies with fast-growing innovation sectors—are at the forefront of this process, yet the regional dimension of their knowledge economies, especially in India, remains insufficiently studied. This article examines territorial and sectoral patterns of knowledge production and commercialization across Indian states, applying a spatial scientometric approach. The analysis draws on data from Scopus, Intellectual Property India, and the National Manufacturing Innovation Survey (2017–2022), aligned with India’s national development priorities. The study explores how regional scientific output relates to inventive and innovation activity. The results show a strong positive link between scientific productivity and both patenting and innovation, with a particularly strong connection between regional knowledge production and inventive activity. The strength of this link varies by field: the spatial distribution of patents closely aligns with publication centres in natural sciences, life sciences, and medicine, but shows the weakest association with arts and humanities. Innovation indicators—such as India’s Industrial Innovation Index and the number of innovative firms—are most strongly linked to output in life sciences and medicine as well as social sciences and management. These findings underscore the potential of scientometric indicators to complement traditional measures of innovation, particularly in data-scarce regional contexts. They offer empirical support for integrating bibliometric data into regional STI assessments and for forecasting innovation potential at the subnational level.